Development of Client-Server System of Remote Access Control to the Premises on the Basis of Mesh-Network (Моделювання, керування та інформаційні технології, 2019)
This article about the system of remote accesscontrol to the premises on the basis of Mesh-network. Theoperating principle of the system and the MESH network aredescribed here. It will also talk about the MESH network andcompare it with other network topologies.